Type and Quantity Of Marine Debris At Selected Public Beaches In Sabah (Tg. Aru & Kosuhoi) During Different Monsoon Seasons - Julyus Melvin, Mobilik; Teck-Yee, Ling; Mohd Lokman, Bin Husain; Ruhana, Hassan (Universiti Malaysia Sabah, 2017)
Marine debris is widely distributed at the coastal area of the global oceans, but their specific sources, quantities and distribution remains inconclusive. Although the threat from marine debris pollution has beginning to be recognized in Malaysia, comprehensive studies are still lacking to document the pollution. This study adopted a standard method of beach marine debris survey to assess the type, amount and sources of debris on a one kilometer section in Tg. Aru and Kosuhoi beaches, Sabah, during surveys in December 2012 (northeast monsoon, NEM), May 2013 (intermediate monsoon, IM) and July 2013 (southwest monsoon, SWM). The mean total debris items was 1,220±532 item/km and weighing at 52.8±17.2 kg/km, where, Kosuhoi beach (1,241 item/km or 57 kg/km) received substantially greater quantities of debris compared to Tg. Aru beach (1,199 item/km or 48 kg/km). Total debris item was more abundant during SWM (1,789 item/km) compared to NEM (1,139 item/km) and IM (733 item/km) seasons. Plastic category items were the most numerous amounting to 1,057 item/km (86.64%) in total debris item. Clear plastic bottles, food wrappers, plastic fragments, coloured plastic bottles and cups were the most abundant objects collected which they contributed 606 item/km (49.69%) from the total item collected. The main source of debris items abundance was from common source which contributed 52% from the total debris items, whereas, those from terrestrial and marine sources contributed 32% and 16% respectively. The high percentage of terrestrial and common sources debris requires marine environment stakeholders to diversify their approach and priority in mitigating this alarming result especially during SWM period. Awareness program is an effective preventive measure that should be continued and intensified. However, the program should focus on target group to ensure the awareness effectiveness to reduce if not totally eliminate the debris in the marine environment.